Studies of the Electromagnetic Calorimeter with projective geometry for the MPD/NICA. (November 2019) - Dabrowska, B.; Krechetov, Yu.; Kulikov, V.; Martemianov, M.; Tyapkin, I.; Zinchenko, A.
Abstract: A projective geometry description of the MPD Electromagnetic Calorimeter (ECal) has been developed and implemented within the MpdRoot software framework. Using this package, characteristics of the detector were studied by Monte Carlo methods. Information about energy and spatial resolution as well as registration efficiency was obtained for different clustering procedures. One module of the detector, developed at JINR, was tested using electron beam at DESY. Energy scan for this prototype was carried out to estimate detector linearity. Results of the simulations and beam tests are presented. A post-publication change was made to this article on 16 Mar 2020 to correct an author name and add a funding acknowledgement.